Identifying birth asphyxia risk factors: Case-control study of new-borns delivered at public health institutions in Gedeo Zone, Ethiopia - Getachew Mergia; Getnet Melaku (Global Pediatrics)
Background: Birth asphyxia, a global health issue causing insufficient oxygen supply, causes around 900,000 annual deaths worldwide. This study aimed to identify risk factors for birth asphyxia in new-borns delivered at public health institutions, reducing neonatal mortality. Methods: This study used an institution-based, unmatched case-control study design with a total of 354 new-borns. We used descriptive statistics and a logistic regression model to thoroughly evaluate the data and find characteristics linked with birth asphyxia. The data were given using adjusted odds ratios with 95 % confidence intervals to ensure a thorough understanding of the risk variables involved. Result: The study included 119 cases and 235 controls, with a median maternal age of 27 years. Factors contributing to birth asphyxia included mode of delivery and amniotic fluid color, with caesarean section (AOR: 4.706, 95 % CI: 2.132–10.386) and unclear amniotic fluid (AOR: 4.991, 95 % CI: 2.609–9.547) significantly increasing the odds of asphyxia. Conclusion: This study identified significant factors contributing to birth asphyxia, including Caesarean section mode of delivery and unclear amniotic fluid color. These findings highlight the importance of monitoring and managing delivery methods and amniotic fluid status to reduce the risk of birth asphyxia.